A critical pedagogy approach for teaching adult English language learners. Issue 175 (19th December 2022) - Floyd, Joel
Abstract: Critical pedagogy as an instructional approach to teaching and learning focuses on democracy, freedom, and the opportunity to challenge oppressive power structures founded upon hegemonic ideologies. This article presents a critical pedagogy approach to support the instruction of adult English language learners. Such an approach should adopt the following components: Building community, addressing implicit biases, dialogic instruction, reflective teaching, and critical thinking. Implementing a critical pedagogy approach to teaching in the adult English as a second language classroom will prepare the learners to become critical thinkers and learners for life.